2008
DOI: 10.1038/jp.2008.207
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum amyloid A concentrations with those of C-reactive protein and procalcitonin in diagnosis and follow-up of neonatal sepsis in premature infants

Abstract: Objective: The purpose of this study was to determine the role of serum amyloid A (SAA) in diagnosis of neonatal sepsis and evaluation of clinical response to antibiotic therapy. We also aimed to compare the efficiency of SAA with that of C-reactive protein (CRP) and procalcitonin (PCT) in diagnosis and follow-up of neonatal sepsis in preterm infants.Study Design: A total of 163 infants were enrolled in this prospective study. The infants were classified into four groups: group 1 (high probable sepsis), group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 29 publications
(31 reference statements)
3
59
0
2
Order By: Relevance
“…It has been reported that SAA has a very short half-life of between 75 and 90 minutes [29]. We previously showed that SAA was an accurate and reliable marker for the diagnosis and followup of neonatal sepsis [18]. In addition, adult studies reported that the clinical value of SAA was superior or equal to CRP in inflammatory abdominal disorders such as acute pancreatitis [30,31].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that SAA has a very short half-life of between 75 and 90 minutes [29]. We previously showed that SAA was an accurate and reliable marker for the diagnosis and followup of neonatal sepsis [18]. In addition, adult studies reported that the clinical value of SAA was superior or equal to CRP in inflammatory abdominal disorders such as acute pancreatitis [30,31].…”
Section: Discussionmentioning
confidence: 98%
“…Levels of SAA increase up to 1000 fold in the 8 to 24 hours after the onset of inflammation. Serum amyloid A has been shown to be useful in various acute diseases (bacterial, viral, traumatic, rheumatic, and ischemic heart disease) and also in neonatal sepsis [16][17][18]. Recently, we have shown that SAA might be used as an accurate marker in addition to clinical and laboratory findings in the diagnosis of NEC [19].…”
mentioning
confidence: 97%
“…For example, circulating pro-C-type natriuretic peptide may serve as an accurate predictor of sepsis in an exclusive cohort of multiple-traumatized patients without traumatic brain injury (121). Serum amyloid A is an accurate and reliable marker for diagnosis and follow-up of neonatal sepsis and was especially useful at the onset of inflammation for the rapid diagnosis of neonatal sepsis; it performed better than CRP and PCT, which were tested in the same study (122). …”
Section: Biomarkersmentioning
confidence: 99%
“…Five studies, involving a total of 535 neonates, were included in the analysis regarding LOS [25,26,34,35,44]. The pooled (95% CI) sensitivity of PCT for the diagnosis of LOS was 90% (73-97%), and the specificity was 88% (72-96%).…”
Section: Diagnostic Accuracy Of Pct For the Diagnosis Of Losmentioning
confidence: 99%